Understanding Design Effectiveness:3Dimensions in Marketing and Advertising Strategy Using (3D3A Strategic Marketing Model) - Ali, Nashwa Ahmed (International Journal of Membrane Science and Technology, 2023)
3D strategy is a new marketplace construct. That lies in the conceptual idea of 3D-advertising performance as central to effective marketing practice. The study aims to explore the different relations between 3D3A strategic marketing model and advertising strategy to reach effective design in campaign. A multi-methods investigation combines a survey with advanced expertise collected of over of 400 global agencies. The study examined three demographic features of advertising professionals (including but not limited to planning, selling, executing, and improving 3d design solutions in a crowded marketplace). Later, SPSS 26 does frequency analysis and descriptive statistics. As result, the percentage of (56.5%) from study sampling mentioned that 3D3A Marketing strategy is consider as accessible model. The significant effectiveness, constraints, recommendations, and future development were discussed.